Programas físico-esportivos no município de São Carlos (SP) e as pessoas com deficiência: propostas, experiências e limites - Andrade, Andresa Caravage de (2015)
This study aims to identify the sporting programs for people with disability in São Carlos (SP), in order to comprehend the aspects of those citizens looking also at the intersectional interactions, the public policies and at the university role in such context. The idea was to get the perspective from the managers, the related professionals and also from the participants. To do so, the necessary data was collected with the public bodies and the supporting entities. First, it was developed a document analysis to comprehend the public policies to disable people. Then, interviews were carried along with participating observation of the activities to get familiar to the field. The study was developed with some municipal departments (Sport and Leisure, Health, Citizenship and Social Assistance and Education) and also with the NGO Information Movement about Disability, Serviço Social do Comércio (SESC) as well as a city councilman. It was based on 22 interviews with managers, professionals and participants together with approximately 58 hours of participating observation. It can be concluded from these data that in the city there are few people participating of those sporting activities, especially when considering women. In general, the programs are offered only for people with disability and are not well articulated. The municipal Education department offers the oldest and best structured program. The programs are a result from the individual effort of the interviewees than from an effective articulated policy. Many of the interviewed people highlighted the importance of the university to train professionals to carry research and to work with the society. However, they also stressed that there s still a gap in university s part in public policies. They have also drawn the attention to how important it is to value sporting activities and its contribution for social integration and quality of life of people with disability. It was noticed a new look over the disabled body which is affirmed when it can develop itself as an athlete. We can conclude that policies in the area are fragile and are disarticulated, which stress the importance of studies and actions to change this context.